Drought risk and adaptation in the Interior - Morisette, Jeffrey, speaker; Morisette, Jeffrey, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Drought is part of the normal climate variability in the Great Plains and Intermountain Western United States, but recent severe droughts along with climate change projections have increased the interest and need for better understanding of drought science and decision making. The purpose of this study is to understand how the U.S. Department of the Interior's (DOI) federal land and resource managers and their stakeholders (i.e., National Park Service, Bureau of Land Management, Fish and Wildlife Service, Bureau of Reclamation, Bureau of Indian Affairs and tribes, among others) are experiencing and dealing with drought in their landscapes. The Drought Risk and Adaptation in the Interior (DRAI) project is part of a DOI-sponsored North Central Climate Science Center (NC CSC) crosscutting science initiative on drought across the Center's three foundational science areas: 1. Physical climate, 2. Ecosystems impacts and responses, and 3. Human adaptation and decision making. The overarching goal is to learn more about drought within the DOI public lands and resource management in order to contribute to both the NC CSC regional science as well as providing managers and other decision makers with the most salient, credible, and legitimate research to support land and resource management decisions. Here we will present the project approach along with some initial insights (with a focus on grazing lands and related DOI/tribal resource management) learned from the research to date along with its utility for climate adaptation.
Drought risk and adaptation in the Interior (DRAI)
Moderator: Jeffrey Morisette.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses